Spray-dried microparticles of turmeric extract for improved delivery and low toxicity - Chutha Takahashi Yupanqui; Anunya Suksanga; Sutasinee Ardhanwanich; Suwipa Ungphaiboon (Pensoft Publishers, 2024)
This study aimed to enhance the delivery of turmeric by encapsulating its extract within microparticles using chitosan and mannitol through the spray drying technique and to assess their acute oral toxicity. The resulting microparticles were spherical, with an average diameter of 4 microns, and comprised 17% curcuminoids and 4% ar-turmerone. In vitro studies demonstrated that these microparticles had a higher release rate of curcuminoids compared to raw turmeric extract and preserved antioxidant activity. In the acute toxicity study, conducted in Wistar rats with a single dose of 2,000 mg/kg, no acute toxic symptoms were observed. According to the Globally Harmonized System of Classification and Labeling of Chemicals, the microparticles were categorized as having relatively low acute toxicity (category 5). These findings support the potential utility of the microparticles in dietary supplements and pharmaceutical applications due to their effective delivery properties and safety profile.